Potrait of Islam Culture and Arabic Literature in Italy - Syafina, Hanna Izzah; Bahruddin, Uril; Sutaman, Sutaman (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University (UIN) Jakarta, 2024)
The arrival of Islam in Italy in the seventh century led to cultural acculturation and changes in several areas of life, such as literature, culture and language. The aims of this study are to: (1) Describe the process of the arrival of Islam in Italy; (2) Describe the influence of Islamic and Arabic culture in Italy. and (3) explaining the development of Arabic science and literature in Italy. This research is included in the descriptive qualitative research with a literature study approach and the data collection techniques used are reading techniques and note-taking techniques. The results of this study are: (1) The process of the arrival of Islam in Italy began when Caliph Othman bin Affan sent the prime minister Muawiyah bin Abi Sufyan to attack Sicily in 652 AD. (2) There are traces of Islamic culture in the architecture of the city in the form of narrow alleys that follows the ancient Arabic style of the city of Amalfi, and the assimilation of Italian words of Arabic origin is close to 300 words; And (3) in the development of scientific and literary journals, Muslim scientists have certainly produced various major works which later became references for Western scientists. Besides that, Arabic literature also entered and developed in Sicily which became a heaven for scholars such as al-Jabr wa Maalaka, Firdaus al-Hikmah, Al-Hawi. Apart from that, Arabic literature also entered and developed in Sicily, becoming a paradise for scholars, such as the story of Layla Majnun which was outlined in the book The Secretum by Petrarch and ST. Augustine.